Pengaruh Hukum Adat (Living Law) terhadap Keputusan Hakim dalam Perkara Perdata Waris : Studi Kasus dalam Putusan Pengadilan Negeri Nomor: 225/Pdt.G/2009/PN. MDN - Lelianta Sembiring , Ariesti; runtung; maria (CV Rewang Rencang, 2026)
The application of Karo customary law adhering to a patrilineal system has led to inheritance disputes regarding the position of daughters as heirs and the status of inherited assets. This research analyzes the Medan District Court Decision Number 225/Pdt.G/2009/PN.Mdn using a normative juridical method with a descriptive analytical approach. The core dispute concerns whether the contested object constitutes inheritance property or has been transferred as a gift and customary marriage payment based on the impal customary relationship. The research findings indicate that the panel of judges prioritized formal evidence and the principle of legal certainty based on national civil law and Supreme Court jurisprudence over local customary law considerations.